IMPROVING THE SPEED-STRENGTH TRAINING OF STUDENTS THROUGH TRACK AND FIELD EXERCISES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Endurance development is a key area of student physical training, particularly in sports pedagogical education. Athletics, as a fundamental sport, offers ample opportunities for developing and improving various types of endurance, including general, specialized, and speed. The purpose of this study is to analyze the pedagogical aspects of endurance development in students during athletics training. This paper examines methodological approaches to organizing the educational and training process aimed at enhancing the body's functional capabilities, improving physical performance, and developing stable motor skills. Particular attention is paid to the use of various athletics exercises, such as middle- and long-distance running, interval training, cross-training, and cyclic exercises. The results of the study demonstrate that the systematic use of athletics techniques in combination with pedagogically sound training methods contributes to the effective development of endurance in students. The findings confirm the importance of an integrated approach to organizing athletics classes in higher pedagogical education.